Administer as a Tool to Improve Investment Efficiency of Direct Taxation of Enterprises (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article proves the role of the administration of direct taxes in raising investment efficiency of direct taxation. The authors systematically analyzed and scientific approaches to defining the essence of the concept of «tax administration» and singled out their main destinations. The structure of the administration of direct taxes entities and singled macroeconomic and microeconomic components. Based on statistical data analysis efficiency of direct taxation in Ukraine. The basic directions of increase of efficiency of administration of direct taxes on businesses as a tool for growth of the investment efficiency of direct taxation of business entities.
Keywords: investment effectiveness of direct taxation, direct taxes, administration, administrative structure of direct taxes, the efficiency of direct taxation